The Padre Gomez Elementary School an institutional case study - Rivera, Josephine C. (s.n.], 1966)
This study provided an empirical description of an organization, a pilot elementary school, the Padre Gomez Elementary school, to determine how an elementary school fulfills its role in Philippine society.